How to Avoid Coronary Occlusion During TAVR Valve-in-Valve Procedures - Valvo, Roberto; Costa, Giuliano; Barbanti, Marco (Frontiers in Cardiovascular Medicine, 2019)
Transcatheter aortic valve-in-valve replacement has been recently reported as a less-invasive alternative to re-do surgery in patients with bioprosthetic valve failure. Although procedural success is achieved in the great majority of patients, this therapy is associated with several potential complications, and coronary occlusion is one of the most feared. This is a rare event, but it is associated with an extremely poor prognosis. In this review, the mechanisms, the identification of patients at high risk, the primary prevention strategies, and treatment of coronary occlusion will be discussed.